The interplay of subjective social status and essentialist beliefs about cognitive aging on cortisol reactivity to challenge in older adults. (9th May 2016) - Weiss, David; Weiss, Mona
Abstract: Older adults are more likely than younger adults to experience stress when confronted with cognitive challenges. However, little is known about individual differences that might explain why some older adults exhibit stronger stress responses than others. We examined the interplay of two social‐cognitive factors to explain older adults' cortisol reactivity: (1) subjective social status, and (2) essentialist beliefs about cognitive aging. We hypothesized that, depending on whether older adults believe that aging‐related cognitive decline is inevitable versus modifiable, low subjective social status should lead to stronger or weaker cortisol reactivity. Using longitudinal data, we assessed the impact of cognitive challenges on stress reactivity in a sample of older adults ( N  = 389; 61–86 years). As predicted, regression analyses confirmed that 44 min after cognitively challenging tasks, older adults exhibited a significantly different cortisol reactivity depending on their subjective social status and their essentialist beliefs about cognitive aging. Specifically, older adults with low subjective social status and high essentialist beliefs showed a significantly elevated cortisol reactivity. We discuss the role of essentialist beliefs about cognitive aging to predict when and why high versus low subjective social status leads to stress responses in older adults.